Penerapan PSAK Adopsi IAS 41 Agriculture - Ariyanto, Stefanus; Sukendar, Heri; Kurniawati, Heny (Bina Nusantara University, 2014)
This study aims to determine whether the application of PSAK adopted from IAS 41: Agriculture should be applied to State-Owned Enterprises, especially the plantation SOE. So that the SOE financial information produced becomes more useful for decision-making. Furthermore, this study wants to answer what benefits can be obtained from the implementation of this standard on the plantation-based SOE. The main characteristic of IAS is the use of fair value model for biological assets owned by the agriculture-based entity. The use of this model raises a lot of controversy, primarily, associated with relevant quality and reliability of the information it produces. Research used qualitative method with data collection through literature study, survey, interview, and observation. Survey and interview were divided into two major parts, which were: on the compilers of financial statements and the stakeholders. From this study it can be concluded that the PSAK based on IAS 41 have not to be implemented yet in the near future due to IAS 41 will undergo quite significant revision. Currently, the State-Owned Enterprises could use the PSAK plantation SOE that has been issued.